1957
DOI: 10.1016/0006-3002(57)90141-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectrophotometry of reduced phosphopyridine nucleotide in intact cells in the near-ultraviolet and visible region

Abstract: TRUE SUBSTRATES FOR ALKALINE PHOSPHATASE 19 o.o16 M/~-glycerophosphate where it might be assumed that substrate formation is fast enough so that it is no longer rate-controlling. In addition to the cases above, Ross and his associates 3 have reported variation in pH optima for alkaline phosphatase activity with substrate concentration for phenyl disodium phosphate, adenylic acid, fructose-I,6-diphosphate, fructose-6-phosphate, and ribonucleic acid. The same analysis may be applied to these; and the "true" subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0
1

Year Published

1959
1959
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(113 citation statements)
references
References 5 publications
5
107
0
1
Order By: Relevance
“…Early observations of metabolic oscillations in yeast (3)(4)(5) and our own investigation of oscillations of NADH and sarcolemmal K,ATP current in substrate-deprived heart cells (6) provide evidence that such phenomena can be observed in intact cells. In our previous work, modulation of the amplitude and͞or frequency of the oscillations by external glucose led to the hypothesis that they were driven by a glycolytic oscillator, but the predominantly mitochondrial origin of the NADH f luorescence in cardiomyocytes (7) suggested that metabolic transients in oxidative phosphorylation were also present.…”
mentioning
confidence: 70%
“…Early observations of metabolic oscillations in yeast (3)(4)(5) and our own investigation of oscillations of NADH and sarcolemmal K,ATP current in substrate-deprived heart cells (6) provide evidence that such phenomena can be observed in intact cells. In our previous work, modulation of the amplitude and͞or frequency of the oscillations by external glucose led to the hypothesis that they were driven by a glycolytic oscillator, but the predominantly mitochondrial origin of the NADH f luorescence in cardiomyocytes (7) suggested that metabolic transients in oxidative phosphorylation were also present.…”
mentioning
confidence: 70%
“…Since its introduction by the groups of Duysens [24] and Chance [25,26] fluorescence a t NADH-specific wavelengths has been abundantly used on a qualitative basis on a variety of intact tissues or cell preparations [26a]. The calibration of surface fluorescence derived from the cytosolic NADH system with the help of specific transitions and internal standards is presented here with the intention of providing an example.…”
Section: Discussionmentioning
confidence: 99%
“…1 The NADH autofluorescence has been utilized extensively in the past for noninvasive assessment of tissue metabolic state and oxygenation. 2,3 In addition to linear excitation of NADH fluorescence, a relatively small but sufficient two-photon absorption cross section exists in the near-infrared spectrum from 700 to 750 nm, 4 which allows two-photon laser scanning microscopy (TPLSM) imaging of NADH fluorescence. [4][5][6][7][8][9] The advantages of TPLSM imaging for in vivo, depth-resolved high-resolution imaging in highly scattering brain tissue make TPLSM imaging of NADH fluorescence very attractive for investigating brain metabolism.…”
Section: Introductionmentioning
confidence: 99%